EVOLVING TRENDS IN KNOWLEDGE MANAGEMENT INNOVATION: AN INDEX-KEYWORD ANALYSIS (2000–2024) - Omar , Mohd Adan; Ammber Nosheen , Ammber Nosheen (Journal of Islamic, Social, Economics and Development, 2024)
Over the past few decades, there has been a notable growth in knowledge management (KM) innovation due to shifting organisational needs and advancements in research. This study thoroughly reviews the current developments in KM innovation, emphasising organisational implementations and progressions. Effective KM innovation is significant because it can improve modernization, organizational learning, and strategic decision-making. This article employed bibliometric keyword analysis to focus on trend index keyword analysis, using a sample of 1,287 Scopus-indexed journals in English, specifically examining computer science articles published from 2000 to 2024. The analysis reveals a wide range of keywords associated with KM innovation. Yet, advancements in KM innovation will continue to be important and central in 2024, underscoring their continued significance in modern organizational environments. To help organisations leverage knowledge as a strategic asset, the findings offer insightful information on the opportunities and obstacles of adopting successful KM innovation initiatives. This study adds to the current conversation on KM innovation in modern businesses by providing a thorough summary of these advancements, highlighting important topics of interest and potential future research areas.